2004
DOI: 10.1590/s0004-282x2004000200021
|View full text |Cite
|
Sign up to set email alerts
|

Transtornos relacionados ao uso de álcool em 1901 pacientes atendidos no pronto socorro municipal de Taubaté no ano 2000: contribuição para educação sociocêntrica em neurologia

Abstract: RESUMO -A educação médica deve privilegiar temas prevalentes; os transtornos relacionados ao álcool são um deles. Nosso objetivo foi determinar a freqüência dos transtornos relacionados ao consumo do álcool e verificar se um mesmo paciente apresentou mais de um transtorno, contribuindo para educação sociocêntrica. Foi estudo retrospectivo transversal em que foram analisadas as fichas de atendimento com relato de consumo de álcool,em pronto socorro,no ano 2000 (1901 casos).Os efeitos diretos do álcool foram enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
2
Order By: Relevance
“…Ferri-De-Barros et al. 11 observed that alcohol consumption causes damages to the digestive tract with appearance of symptoms of ulcer and other alcohol-related diseases, such as esophagitis, chronic pancreatitis, gastritis, among others.…”
Section: Resultsmentioning
confidence: 99%
“…Ferri-De-Barros et al. 11 observed that alcohol consumption causes damages to the digestive tract with appearance of symptoms of ulcer and other alcohol-related diseases, such as esophagitis, chronic pancreatitis, gastritis, among others.…”
Section: Resultsmentioning
confidence: 99%
“…Das mulheres atendidas em Hospital Ensino, neste trabalho, a faixa etária mais prevalente foi a de 20 a 49 anos (58.3%), e a segunda foi menos de de álcool. Quando analisadas apenas as mulheres, a maior prevalência foi dos 21 aos 30 anos de idade (10) .…”
Section: Resultsunclassified
“…Em Taubaté, de acordo com o horário de entrada no Pronto Socorro, predominou o período noturno, das 18 às 24 h (29.3%). Isto pode evidenciar maior consumo após a jornada de trabalho (10) .…”
Section: Variáveisunclassified
“…As a nutritional treatment, a diet with little pulp, non-stimulant, energy, and other nutrients (especially protein, vitamins A, C, E, and iron) is sufficient, the number of meals is high, and the proportion of nutrients is low (85). Ferri-De-Barros et al (86) reported that chronic alcohol consumption can lead to various gastrointestinal problems, including esophagitis, chronic pancreatitis, and ulcers. Reis et al (87) reported that smoking has been linked to decreased mucus and bicarbonate secretion, thereby increasing the risk of ulcer formation.…”
Section: Recommendations For Nutritional Therapy In Gastritismentioning
confidence: 99%